Case Report: A Case Series of Rare High-Type Anorectal Malformations With Perineal Fistula: Beware of Urethral Involvement - Jun, Lim Hui; Jacobsen, Anette; Rai, Rambha (Frontiers in Surgery, 2021)
Anorectal malformations (ARMs) are among the more frequent congenital anomalies encountered in paediatric surgery where the majority are diagnosed in the early neonatal period. The etiology of ARM remains uncertain and is likely to be multifactorial. A majority of ARM result from abnormal development of the urorectal septum in early fetal life. There is a wide spectrum of presentation ranging from low anomalies with perineal fistula to high anomalies mandating complex management. To develop a system for comparable follow-up studies, the Krickenbeck classification was introduced according to the type of fistula. According to the Krickenbeck classification of ARM, those with a rectoperineal fistula are classified as low-type ARM and are usually managed with a perineal anoplasty without colostomy. In this case series, we describe two rare cases of distinct high and intermediate ARM with rectoperineal fistulas which were thought to be low-type ARM but were subsequently found to have urethral involvement. Our cases consisted of a high and intermediate ARM which were successfully treated with PSARP as described. These cases exemplified rare variants of ARM where rectoperineal fistula can be associated with high-type anomalies. Rare- variant ARM with rectopenile or rectoscrotal fistula can be associated with high-type anomalies in contrary to classical rectoperineal fistulae. A high index of suspicion should remain in cases with previous urinary tract infection despite normal imaging. Careful planning is also needed with consideration of possible need for urethral repair during anoplasty which was needed in both our cases.